Harnessing Neurons in Order to Get Rid from the Gravitation in Buddhist Point of View - Khemananda, Manakada (University of Sri Jayewardenepura, Nugegoda., 2015)
With the assistance of sophisticated apparatus scientists have accomplished jaw dropping experiments regarding the human organs and the breakthroughs of some experiments concerned with mind are occasionally beyond the range of human understanding. Accordingly, no more human mind is a hidden organ though penetrable; its structure and function are explicit and it can be malfunctioned due to diseases infected internally or externally. In contrast, evidently, by the present time Buddhism can be recognized as the fastest growing religion around the globe due to its mind based peculiarities, scientific approve and compatibility with modern science. It doesn’t emphasize much about the structure of the mind as it is in the modern scientific field though the mind cultivation. As to scientists mind should be realized the collection of 100 billion neurons and it is functioned by ten uninterrupted external and internal faculties. Hence it is the place to receive negative alike positive stimulations which cause to create misguided and sophisticated individuals. To be a sophisticated and empathetic individual practice of love, compassion, generosity, meditation etc. are prescribed specially by the neuroscience. Interestingly, Buddhism also advocated it before two thousand and six hundred years without using any single external instrument and its incredible results extend beyond the range of scientific knowledge. With reference to both traditions human mind is malleable therefore, in this paper I’m going to examine the transparency of Buddhism in experiencing the authentic development of the human mind.
Keywords: Mind; Gravitation; Levitation